Improved Dissolution and Oral Bioavailability of Valsartan Using a Solidified Supersaturable Self-Microemulsifying Drug Delivery System Containing Gelucire® 44/14 - Dong Jun Shin; Bo Ram Chae; Yoon Tae Goo; Ho Yub Yoon; Chang Hyun Kim; Se Il Sohn; Dongho Oh; Ahram Lee; Seh Hyon Song; Young Wook Choi (MDPI AG, 2019)
To improve the dissolution and oral bioavailability of valsartan (VST), we previously formulated a supersaturable self-microemulsifying drug delivery system (SuSMED) composed of Capmul® MCM (oil), Tween® 80 (surfactant), Transcutol® P (cosurfactant), and Poloxamer 407 (precipitation inhibitor) but encountered a stability problem (Transcutol® P-induced weight loss in storage) after solidification. In the present study, replacing Transcutol® P with Gelucire® 44/14 resulted in a novel SuSMED formulation, wherein the total amount of surfactant/cosurfactant was less than that of the previous formulation. Solidified SuSMED (S-SuSMED) granules were prepared by blending VST-containing SuSMED with selective solid carriers, L-HPC and Florite® PS-10, wherein VST existed in an amorphous state. S-SuSMED tablets fabricated by direct compression with additional excipients were sufficiently stable in terms of drug content and impurity changes after 6 months of storage at accelerated conditions (40 ± 2 °C and 75 ± 5% relative humidity). Consequently, enhanced dissolution was obtained (pH 1.2, 2 h): 6-fold for S-SuSMED granules against raw VST; 2.3-fold for S-SuSMED tablets against Diovan® (reference tablet). S-SuSMED tablets increased oral bioavailability in rats (10 mg/kg VST dose): approximately 177⁻198% versus raw VST and Diovan®. Therefore, VST-loaded S-SuSMED formulations might be good candidates for practical development in the pharmaceutical industry.